Diseño e implementación de un plan de mantenimiento eficiente para equipos industriales de grado hospitalario en el centro médico valle de Atriz. (2023)
In the following project which is focused on the implementation of a plan effective maintenance for industrial equipment medical degree from a medical institution services such as the Valle de Atriz medical center and To achieve the objective, 10 points have been established important for the execution and development of the themselves, starting towards the vision of improving the productivity of the teams so that together with the activities carried out in the institution always is to provide an optimal and adequate service health to the community of our region.